The algorithm and program for processing linear spectra - Gavrikov, V.B.; Prokhorets, S.I. (Вопросы атомной науки и техники, 2001)
We present the algorithm, which allows to process linear spectra containing overlapped peaks. The program using this algorithm provides a fast processing procedure for any linear spectra at arbitrary radiation background conditions.